Banal Security Queer Korea in the Time of Viruses - Gitzen, Timothy (AHEAD: Advanced Studies in the Humanities and Social Sciences, 2023)
The decades-long fear of South Korean national destruction has routinized national security and the sense of threat. In present day South Korea, national security includes not only war and the military, but national unity, public health, and the family. As a result, queer Koreans have become a target as their bodies are thought to harbor deadly viruses and are thus seen as carriers of diseases. The prevailing narrative already sees being queer as a threat to traditional family and marriage. By claiming that queer Koreans disrupt military readiness and unit cohesion, that threat is extended to the entire population. Queer Koreans are enveloped by the banality of security, treated as threats, while also being overlooked as part of the nation. What does it mean to be perceived as a national threat simply based on who you would like to sleep with? In their desire to be seen as citizens who support the safety and security of the nation, queer Koreans placate a patriarchal and national authority that is responsible for their continued marginalization. At the same time, they are also creating spaces to protect themselves from the security measures and technologies directed against them. Taking readers from police stations and the galleries of the Constitutional Court to queer activist offices and pride festivals, Banal Security explores how queer Koreans participate in their own securitization, demonstrates how security weaves through daily life in ways that oppress queer Koreans, and highlights the work of queer activists to address that oppression. In doing so, queer Koreans challenge not only the contours of national security in South Korea, but global entanglements of security.